Cholinesterases, carbonic anhydrase inhibitory properties and in silico studies of novel substituted benzylamines derived from dihydrochalcones. (October 2021) - Akıncıoğlu, Akın; Göksu, Süleyman; Naderi, Ali; Akıncıoğlu, Hülya; Kılınç, Namık; Gülçin, İlhami
Abstract: A series of novel urea, sulfamide and N, N -dipropargyl substituted benzylamines were synthesized from dihydrochalcones. The synthesized compounds were evaluated for their cholinesterases and carbonic anhydrase inhibitory actions. The known dihydrochalcones were converted into four new benzylamines via reductive amination. N, N -Dipropargylamines, ureas and sulfamides were synthesized following the reactions of benzylamines with propargyl bromide, N, N -dimethyl sulfamoyl chloride and N, N -dimethyl carbamoyl chloride. The novel substituted benzylamines derived from dihydrochalcones were evaluated against some enzymes such as human erythrocyte carbonic anhydrase I and II isoenzymes (hCA I and hCA II), acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). The novel substituted benzylamines derived from dihydrochalcones exhibited Ki values in the range of 0.121–1.007 nM on hCA I, and 0.077–0.487 nM on hCA II closely related to several pathological processes. On the other hand, Ki values were found in the range of 0.112–0.558 nM on AChE, 0.061–0.388 nM on BChE. As a result, novel substituted benzylamines derived from dihydrochalcones showed potent inhibitory profiles against indicated metabolic enzymes. In addition, Induced-Fit Docking (IFD) simulations and ADME prediction studies have also been carried out to elucidate the inhibition mechanisms and drug-likeness of the synthesized compounds. Therefore, these results can make significant contributions to the treatment of some global diseases, especially Alzheimer's diseases and glaucoma, and the development of new drugs. Graphical Abstract: ga1 Highlights: Four ureas, four sulfamides and four dipropargyl amine derivatives were obtained from benzyl amines. The compounds demonstrated nanomolar inhibition level against AChE and BChE enzymes. The compounds exhibited powerful inhibition against CA I and CA II in subnanomolar levels. In addition, Induced-Fit Docking (IFD) simulations and ADME prediction studies have also been carried out. The inhibition mechanisms and drug-likeness of the synthesized compounds were elucidated.